Comparative constructions in Bisha Colloquial Arabic: a case study - Alharthy, Fatema (Frontiers in Language Sciences, 2025)
IntroductionComparative constructions are a core syntactic and semantic feature across Arabic varieties, yet their dialectal realizations remain unevenly documented. Despite extensive research on Modern Standard Arabic (MSA) and major dialects, the comparative system of Bisha Colloquial Arabic (BCA)—a distinct southern Saudi dialect—has received virtually no systematic linguistic attention. This study addresses this critical gap by identifying the unique forms and functions of comparative constructions in BCA and situating them within the broader spectrum of Arabic dialectology, with reference to parallels and divergences from MSA and other regional varieties.MethodologyData were collected from undergraduate student discourse during grammar class interactions and social media content, including TikTok and X (formerly Twitter). Comparative expressions were identified, systematically extracted, and categorized into distinct structural types: simple comparatives, complex comparatives, equality comparisons, non-scalar comparisons, quantitative and qualitative comparisons, intensified comparisons, adverbial and clausal comparisons, and comparative correlatives. A qualitative analysis was conducted to describe the patterns and functions of these constructions in BCA.ResultsThe analysis revealed that BCA employs a versatile and adaptive system of comparative constructions, characterized by simplicity and pragmatic efficiency. Unlike the rigid grammatical rules of MSA, which heavily rely on the classical ʔafʕal pattern with case markings, BCA prioritizes syntactic flexibility and contextual clarity. Markers such as ʔaktar (“more”), ʔagall (“less”), and informal terms like zaay and kan (“like”) were prominent. The dialect incorporates nominal, adverbial, and clausal comparisons, enabling speakers to convey equality, difference, and intensification effectively. Expressions such as b-kathiir (“much more”) and b-milyoon marrah (“a million times”) enhance expressiveness, while correlatives like kul ma (“the more”) highlight causal and proportional relationships. These trends align with patterns observed in other Arabic dialects, such as Egyptian and Levantine Arabic, which emphasize accessibility in spoken communication.DiscussionThe findings suggest that BCA adapts traditional grammar to prioritize conversational needs, striking a balance between practicality and clarity. This research contributes to the broader understanding of Arabic dialectal variation and highlights the role of colloquial forms in meeting modern communicative demands. The results offer valuable insights for linguists, translators, and educators working with Arabic dialects.